Mechanisms sensitive to different drugs mediate a pro-adhesive and pro-thrombotic platelet phenotype in anti-phospholipid syndrome - Marina Camera; Marta Brambilla; Paola Adele Lonati; Alessia Becchetti; Claudia Grossi; Kevin Nallio; Arianna Da Via; Laura Trespidi; Maria Orietta Borghi; Francesco Tedesco; Pier Luigi Meroni (Haematologica)
Antiphospholipid antibodies (aPL) mediate platelet- and leukocyte-interaction with damaged endothelium, contributing to antiphospholipid syndrome (APS) vasculopathy. This study aimed to understand the mechanisms sustaining the pro-adhesive/-thrombotic platelet phenotype and the in vitro effects of different drugs.